Moderation of Firm Size: Financial Performance on Disclosure of Corporate Social Responsibility - Sylvia Sylvia; Rustan DM; Muhammad Idris (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study aims to determine and analyze the impact of financial performance on corporate social responsibility disclosure, with company size serving as a moderator. The population of this survey consisted of all 25 retail trade subsector companies listed on the Indonesia Stock Exchange between 2014 and 2016. The total number of entities included in this study was 43. As research samples, 32 quarterly financial reports from two corporations constituted the complete data processed. The secondary data used in the study were the company's financial statements obtained through documentation techniques. Several phases of testing will be performed on the data in this study, including descriptive statistical tests, selecting the best model (chow test, Hausman test, and lm test), and testing all hypotheses via partial tests (t-tests), moderation tests, and coefficient of determination tests. This study's findings indicate that financial performance as measured by ROA has a positive and statistically significant effect on CSR disclosure of retail trade on the Indonesia Stock Exchange. While company size can moderate the impact of financial performance proxy ROA on CSR disclosure of retail business on the Indonesia Stock Exchange, ROA has a positive and significant effect.